TEAMWORK ON THE SOCCER FIELD : AND OTHER SOCCER SKILLS - Scheff, Matt (Sports Illustrated Kids, 2022)
Winning is fun, but it takes more than winning to be a real superstar. Today's soccer superstars know it takes talent, skill, and teamwork on and off the field. This Sports Illustrated Kids title combines fast-paced action, famous plays, and SEL skills to show what sets your favorite athletes and teams apart.